Narativni teksti o Borisu in Glebu med posredovanjem političnega zgleda in tolmačenjem zgodovine - Malmenvall, Simon (Slavistična revija, 2017)
The two princely brothers Boris and Gleb were the first canonized East Slavic saints (known as passion-bearers). The narrative/literary texts dedicated to them and written until the beginning of the twelfth century, among which the Lesson on Boris and Gleb stands out stylistically and conceptually, are defined by two fundamental characteristics: by offering a sacralized political example during the period of growing political instability in East Slavic territory and by stressing the spiritual "maturity" of Kievan Rus' in the context of salvation history. The existence of princely or royal saints (i.e., passion-bearers) cannot be regarded as a special feature of East Slavic medieval culture; this kind of sainthood was generally present in the lands of the northern and eastern European peripheries of the time.
Keywords: Boris and Gleb; Branje o Borisu in Glebu; Old Russian literature; passion-bearers; Rusisan saints; ruska zgodovina; ruski svetniki; salvation history; stara ruska književnost; strastotrpci; zgodovina odrešenja